Evolutionary conservation of DNA methylation in CpG sites within ultraconserved noncoding elements. Issue 1 (2nd January 2018) - Colwell, Mathia; Drown, Melissa; Showel, Kelly; Drown, Chelsea; Palowski, Amanda; Faulk, Christopher
ABSTRACT: Ultraconserved noncoding elements (UCNEs) constitute less than 1 Mb of vertebrate genomes and are impervious to accumulating mutations. About 4000 UCNEs exist in vertebrate genomes, each at least 200 nucleotides in length, sharing greater than 95% sequence identity between human and chicken. Despite extreme sequence conservation over 400 million years of vertebrate evolution, we show both ordered interspecies and within-species interindividual variation in DNA methylation in these regions. Here, we surveyed UCNEs with high CpG density in 56 species finding half to be intermediately methylated and the remaining near 0% or 100%. Intermediately methylated UCNEs displayed a greater range of methylation between mouse tissues. In a human population, most UCNEs showed greater variation than the LINE1 transposon, a frequently used epigenetic biomarker. Global methylation was found to be inversely correlated to hydroxymethylation across 60 vertebrates. Within UCNEs, DNA methylation is flexible, conserved between related species, and relaxed from the underlying sequence selection pressure, while remaining heritable through speciation.